The role of enhanced recovery after surgery (ERAS) in promoting quality improvement and patient safety in pediatric urology - Darren Ha; Darren Ha; Kelly T. Harris; Kelly T. Harris; Kelly T. Harris; Megan A. Brockel; Kyle O. Rove; Kyle O. Rove; Kyle O. Rove (Frontiers in Urology, 2023)
Enhanced Recovery After Surgery (ERAS) is a set of evidence-based, multidisciplinary protocols that aim to improve the perioperative experience for patients by optimizing factors before, during, and after surgery. Originally developed for adult colorectal surgery, these protocols have expanded and been adopted into the pediatric surgical realm, including pediatric urology. Preoperative interventions are directed toward reducing physiologic and emotional stress prior to surgery, including preoperative education and decreased duration of fasting. Intraoperative interventions are designed to support physiologic homeostasis through maintenance of normothermia and euvolemia, use of regional anesthesia, and minimizing placement of drains. Postoperative interventions seek to reduce the physiologic burden of surgery and restore patients to their functional baseline through early oral intake, early mobilization, and opioid-sparing, multimodal analgesia. ERAS has demonstrated efficacy and safety across a wide variety of surgical subspecialties. In pediatric urology, ERAS has led to earlier return of bowel function, decreased opioid utilization, and shorter hospital length of stay, without an increase in complications compared to prior standard of care. ERAS can thus be seen as a system through which quality improvement (QI) initiatives can be designed and tailored to particular settings and patient populations. This review aims to summarize current data in pediatric urology regarding ERAS elements in the context of QI and patient safety. It will discuss the barriers and future directions of this field, including collaboration with implementation science to facilitate adoption of these protocolized measures more widely.